2012
DOI: 10.1097/shk.0b013e31823918c2
|View full text |Cite
|
Sign up to set email alerts
|

LIPOCALIN-2 Is a Major Acute-Phase Protein in a Rat and Mouse Model of Sterile Abscess

Abstract: Lipocalin-2 (LCN-2) is a 25-kDa secretory protein currently used as a biomarker for renal injury and inflammation. Its source and cause of the increased serum levels are unclear. The current study compares LCN-2 gene expression with known major acute-phase proteins in the liver in a rat and mouse model of turpentine oil-induced sterile abscess. Serum LCN-2 concentrations increased dramatically up to 200-fold (20 μg/mL) at 48 h after turpentine oil injection. A strong elevation of LCN-2 mRNA in rat liver was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 23 publications
6
48
1
Order By: Relevance
“…From the observation of the slightly elevated number of circulating white blood cells and the indications of kidney injury in wild-type animals exposed to hypoxia, we expected an inflammatory response. The investigation of the renal expression of several proinflammatory cytokines (e.g., TNF-␣ and IL-6), chemokines (e.g., MCP1 and MIP2), and the acute phase protein SAA, which have been previously shown to be increased after induction of AKI and to mediate ischemic AKI (2,51,53), confirmed the hypothesis that only in wild-type mice does hypoxia induce an inflammatory response. Among profibrotic changes, which are inducible by KIM1, it has been also shown that KIM1 expression correlates with MCP1 expression (26).…”
Section: Influence Of Systemic Hypoxia On Clinical and Laboratory Parmentioning
confidence: 59%
“…From the observation of the slightly elevated number of circulating white blood cells and the indications of kidney injury in wild-type animals exposed to hypoxia, we expected an inflammatory response. The investigation of the renal expression of several proinflammatory cytokines (e.g., TNF-␣ and IL-6), chemokines (e.g., MCP1 and MIP2), and the acute phase protein SAA, which have been previously shown to be increased after induction of AKI and to mediate ischemic AKI (2,51,53), confirmed the hypothesis that only in wild-type mice does hypoxia induce an inflammatory response. Among profibrotic changes, which are inducible by KIM1, it has been also shown that KIM1 expression correlates with MCP1 expression (26).…”
Section: Influence Of Systemic Hypoxia On Clinical and Laboratory Parmentioning
confidence: 59%
“…The first two are synthesized during differentiation of neutrophilic granulocytes and stored in specific granules that can be released upon activation [42, 48]. LCN2 has recently been reported to be a major APP in rat and mouse, as mRNA levels dramatically increase in both leukocytes and liver following inflammation [46, 49, 50]. In the current study, LCN2 mRNA was modestly up-regulated (3-fold), suggesting that this gene should be considered a minor APP in caprine leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal anti-LCN2 antibody, NBPI-05182, (Novus Biologicals) [61] Liver tissue NBP1-05182 (Acris GmbH) [70] Liver tissue Monoclonal anti-LCN2 (Novus Biologicals) [56] Human Urine MAB1757 (R&D Systems) [68] Immuno(fluorescence) staining Mouse Liver tissue Not commercially available antibody [64] Liver tissue AF1857 (R&D Systems)…”
Section: Western Blot Mousementioning
confidence: 99%
“…Not commercially available antibody [46] Rat Liver tissue AF3508 (R&D Systems) [52] Liver tissue AF350 (R&D Systems) [52] Liver tissue Goat polyclonal anti-LCN2 (R&D Systems) [56] Liver tissue Monoclonal anti-LCN2 antibody, NBPI-5182 (Novus Biologicals) [61] ELISA † Mouse Blood serum Mouse LCN2 ELISA-DuoSet Development Kit (R&D Systems) [64] Blood serum Lipocalin-2/NGAL ELISA kit (BioVendor) [49] Rat Blood serum Lipocalin-2 ELISA Bioporto Diagnostics Kit 046 (Bioporto Diagnostics) [56,70] Blood serum ELISA Kit-046 (BioPorto Diagnostics) [61] Human Urine NGAL ELISA kit (BioPorto Diagnostics) [68] Blood serum Human LCN2 ELISA Kit (R&D Systems) [64] Blood serum Lipocalin-2/NGAL ELISA kit (BioVendor) [49] Blood serum Human Lipocalin-2/NGAL Duoset kit (R&D Systems)…”
Section: Western Blot Mousementioning
confidence: 99%